Book Review - Dustin R. Rubenstein (Animal Behaviour, 2026)

Interspecific Competition Reduces Energy Expenditure by Decreasing Intragroup Conflict in a Social Burying Beetle - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)
Assessing the physiological costs of sociality remains challenging due to complex interactions between environmental and social factors. To overcome this challenge, we integrated game theory with empirical research to examine how interspecific competition affects energy expenditure in the cooperatively breeding Asian burying beetle Nicrophorus nepalensis . Our nested tug‐of‐war model made two predictions: beetles facing interspecific competition would experience (1) lower physiological costs due to reduced investment in intragroup conflict, despite increased cooperative effort; and (2) decreasing physiological cost differences between dominance ranks. Using thermal imaging, we analysed body temperature as a proximal indicator of thermogenic effort during carcass work. Results supported our model's two key predictions: beetles competing with blowflies exhibited lower body temperatures, with less pronounced temperature differences between social ranks. Thus, reduced social conflict outweighs the energetic costs of increased cooperation in the face of external threats, providing insights into how environmental conditions shape energy allocation in social species.

Cover Image, Volume 28, Issue 12 - Bo‐Fei Chen; Yi‐Ching Li; Dustin R. Rubenstein; Angèle Rolland; Syuan‐Jyun Sun; Mark Liu; De‐Pei Chen; Sheng‐Feng Shen (Ecology Letters, 2025)

The impact of parental and developmental stress on DNA methylation in the avian hypothalamic–pituitary–adrenal axis - Stefanie J. Siller Wilks; Britt J. Heidinger; David F. Westneat; Joseph Solomon; Dustin R. Rubenstein (Molecular Ecology, 2024)
The hypothalamic–pituitary–adrenal (HPA) axis coordinates an organism's response to environmental stress. The responsiveness and sensitivity of an offspring's stress response may be shaped not only by stressors encountered in their early post‐natal environment but also by stressors in their parent's environment. Yet, few studies have considered how stressors encountered in both of these early life environments may function together to impact the developing HPA axis. Here, we manipulated stressors in the parental and post‐natal environments in a population of house sparrows ( Passer domesticus ) to assess their impact on changes in DNA methylation (and corresponding gene expression) in a suite of genes within the HPA axis. We found that nestlings that experienced early life stress across both life‐history periods had higher DNA methylation in a critical HPA axis gene, the glucocorticoid receptor ( NR3C1 ). In addition, we found that the life‐history stage when stress was encountered impacted some genes ( HSD11B1, NR3C1 and NR3C2 ) differently. We also found evidence for the mitigation of parental stress by post‐natal stress (in HSD11B1 and NR3C2 ). Finally, by assessing DNA methylation in both the brain and blood, we were able to evaluate cross‐tissue patterns. While some differentially methylated regions were tissue‐specific, we found cross‐tissue changes in NR3C2 and NR3C1 , suggesting that blood is a suitable tissue for assessing DNA methylation as a biomarker of early life stress. Our results provide a crucial first step in understanding the mechanisms by which early life stress in different life‐history periods contributes to changes in the epigenome of the HPA axis.

Environmental quality mediates the ecological dominance of cooperatively breeding birds - Yu‐Heng Lin; Ying‐Yu Chen; Dustin R. Rubenstein; Ming Liu; Mark Liu; Sheng‐Feng Shen (Ecology Letters, 2023)
Although social species as diverse as humans and ants are among the most abundant organisms on Earth, animals cooperate and form groups for many reasons. How these different reasons for grouping affect a species' ecological dominance remains unknown. Here we use a theoretical model to demonstrate that the different fitness benefits that animals receive by forming groups depend on the quality of their environment, which in turn impacts their ecological dominance and resilience to global change. We then test the model's key predictions using phylogenetic comparative analysis of >6500 bird species. As predicted, we find that cooperative breeders occurring in harsh and fluctuating environments have larger ranges and greater abundances than non‐cooperative breeders, but cooperative breeders occurring in benign and stable environments do not. Using our model, we further show that social species living in harsh and fluctuating environments will be less vulnerable to climate change than non‐social species.

A chemically triggered transition from conflict to cooperation in burying beetles - Bo‐Fei Chen; Mark Liu; Dustin R. Rubenstein; Syuan‐Jyun Sun; Jian‐Nan Liu; Yu‐Heng Lin; Sheng‐Feng Shen (Ecology Letters, 2020)
Although interspecific competition has long been recognised as a major driver of trait divergence and adaptive evolution, relatively little effort has focused on how it influences the evolution of intraspecific cooperation. Here we identify the mechanism by which the perceived pressure of interspecific competition influences the transition from intraspecific conflict to cooperation in a facultative cooperatively breeding species, the Asian burying beetle Nicrophorus nepalensis . We not only found that beetles are more cooperative at carcasses when blowfly maggots have begun to digest the tissue, but that this social cooperation appears to be triggered by a single chemical cue – dimethyl disulfide (DMDS) – emitted from carcasses consumed by blowflies, but not from control carcasses lacking blowflies. Our results provide experimental evidence that interspecific competition promotes the transition from intraspecific conflict to cooperation in N. nepalensis via a surprisingly simple social chemical cue that is a reliable indicator of resource competition between species.

The oxidative costs of parental care in cooperative and pair-breeding African starlings - Sarah Guindre-Parker; Dustin R. Rubenstein (Oecologia, 2018)

Ecological generalism facilitates the evolution of sociality in snapping shrimps - Katherine C. Brooks; Rafael Maia; J. Emmett Duffy; Kristin M. Hultgren; Dustin R. Rubenstein (Ecology Letters, 2017)
Evidence from insects and vertebrates suggests that cooperation may have enabled species to expand their niches, becoming ecological generalists and dominating the ecosystems in which they occur. Consistent with this idea, eusocial species of sponge‐dwelling Synalpheus shrimps from Belize are ecological generalists with a broader host breadth and higher abundance than non‐eusocial species. We evaluate whether sociality promotes ecological generalism (social conquest hypothesis) or whether ecological generalism facilitates the transition to sociality (social transition hypothesis) in 38 Synalpheus shrimp species. We find that sociality evolves primarily from host generalists, and almost exclusively so for transitions to eusociality. Additionally, sponge volume is more important for explaining social transitions towards communal breeding than to eusociality, suggesting that different ecological factors may influence the independent evolutionary origins of sociality in Synalpheus shrimps. Ultimately, our results are consistent with the social transition hypothesis and the idea that ecological generalism facilitates the transition to sociality.

The ecology of cooperative breeding behaviour - Sheng‐Feng Shen; Stephen T. Emlen; Walter D. Koenig; Dustin R. Rubenstein (Ecology Letters, 2017)
Ecology is a fundamental driving force for the evolutionary transition from solitary living to breeding cooperatively in groups. However, the fact that both benign and harsh, as well as stable and fluctuating, environments can favour the evolution of cooperative breeding behaviour constitutes a paradox of environmental quality and sociality. Here, we propose a new model – the dual benefits framework – for resolving this paradox. Our framework distinguishes between two categories of grouping benefits – resource defence benefits that derive from group‐defended critical resources and collective action benefits that result from social cooperation among group members – and uses insider–outsider conflict theory to simultaneously consider the interests of current group members (insiders) and potential joiners (outsiders) in determining optimal group size. We argue that the different grouping benefits realised from resource defence and collective action profoundly affect insider–outsider conflict resolution, resulting in predictable differences in the per capita productivity, stable group size, kin structure and stability of the social group. We also suggest that different types of environmental variation (spatial vs. temporal) select for societies that form because of the different grouping benefits, thus helping to resolve the paradox of why cooperative breeding evolves in such different types of environments.

Environmental variability and the evolution of the glucocorticoid receptor ( Nr3c1 ) in African starlings - Natalie R. Hofmeister; Dustin R. Rubenstein (Ecology Letters, 2016)
One of the primary ways that organisms cope with environmental change is through regulation of the hypothalamo–pituitary–adrenal ( HPA ) axis, the neuroendocrine system that controls reactions to stress. Variation in genes regulating the HPA axis – particularly the glucocorticoid receptor – may facilitate adaptation to changing climatic conditions by altering expression. Here we examine signatures of selection on the glucocorticoid receptor gene ( Nr3c1 ) in African starlings that inhabit a range of environments, including those with variable climatic conditions. To investigate potential adaptive mechanisms underlying the vertebrate stress response, we sequence the Nr3c1 gene in 27 species of African starlings. Although we find some evidence of positive selection, substitution rate is negatively correlated with variance in precipitation. This suggests climatic cycling in sub‐Saharan Africa may have resulted in lower substitution rates to maintain a successful coping strategy. When environmental conditions fluctuate rapidly, variation in the strength of purifying selection can explain evolutionary rate variation.

Sex‐specific fitness effects of unpredictable early life conditions are associated with DNA methylation in the avian glucocorticoid receptor - Dustin R. Rubenstein; Hannah Skolnik; Alejandro Berrio; Frances A. Champagne; Steven Phelps; Joseph Solomon (Molecular Ecology, 2016)
Organisms can adapt to variable environments by using environmental cues to modulate developmental gene expression. In principle, maternal influences can adaptively adjust offspring phenotype when early life and adult environments match, but they may be maladaptive when future environments are not predictable. One of the best‐studied ‘maternal effects’ is through modification of the offspring's hypothalamic–pituitary–adrenal ( HPA ) axis, the neuroendocrine system that controls responses to stress. In addition to the direct transfer of glucocorticoids from mother to offspring, offspring HPA function and other phenotypes can also be affected by epigenetic modifications like DNA methylation of the glucocorticoid receptor promoter. Here we examine how among‐year variation in rainfall is related to DNA methylation during development and fitness in adulthood in the superb starling ( Lamprotornis superbus) , which lives in a climatically unpredictable environment where early life and adult environments are unlikely to match. We found that DNA methylation in the putative promoter of the glucocorticoid receptor gene is reduced in chicks – particularly in males – born following drier prebreeding periods. Additionally, DNA methylation is lower in males that become breeders than those that never breed. However, there is no relationship in females between DNA methylation and the likelihood of dispersing from the natal group to breed elsewhere. These results suggest that early life conditions may positively affect fitness in a sex‐specific manner through chemical modification of an HPA ‐associated gene. This study is the first to show that epigenetic modifications during early life may influence the fitness of free‐living organisms adapted to unpredictable environments.